Sumber Daya Bersama, Kontestasi, Hadirnya Spirit Berdesa : Studi Kasus Pengelolaan Telaga Jonge Desa Pacarejo, Kabupaten Gunungkidul - Agustinus Sakro Sakro (GOVERNABILITAS (Jurnal Ilmu Pemerintahan Semesta), 2020)
This study describes the efforts of the village government in protecting Telaga Jonge and the conflicts resulting from privatization under the rubric of the tourism village program. The study used an institutional approach guided by qualitative methods using a case study strategy of Jonge Lake Tourism Management in Pacarejo Village, Semanu Gunungkidul. Primary data collection is obtained through in-depth interviews with business actors, village government, managers and local communities, observation and documentation. Secondary data is obtained through books, journals, documents, online media and photos. The results showed that the management of Telaga Jonge indicated that there was private intervention to make the country absent, which was supported by the tourism village program that oriented Pokdarwis. At the same time, it creates disputes because of, by and from the presence of community-based institutions that the program wants. In response to this, the village government took social engineering to protect the conflict and returned Telaga Jonge to the village.